Pengaruh Hedonisme dan Keamanan Transaksi Terhadap Tingkat Penggunaan QRIS Dengan Literasi Keuangan Sebagai Variabel Moderasi - Rahmawati, Rohana Dewi; Gitayuda, M.Boy Singgih; Purnamawati, Purnamawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
This study aims to analyze the influence of hedonism and transaction security on the level of QRIS usage, with financial literacy as a moderating variable. The methodology used is a quantitative approach with a survey method. The population in this study consist of students from the faculty of Economics and Business at Universitas Trunojoyo Madura. The sampling techniqueemployed was purposive sampling with a total of 97 respondents. The research instrument was a closedended questionnaire using a likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, processed through SmartPLS 4 software. The results indicate that hedonism and transaction security significantly influence QRIS usage. However, financial literacy does not moderate the relationship between hedonism or transaction security and QRIS usage. These findings suggest that although financial knowledge is important, it does not necessarily strengthen the relationship between lifestyle or security and QRIS usage behavior.